Using a novel rigid-fluoride polymer to control the interfacial thickness of graphene and tailor the dielectric behavior of poly(vinylidene fluoride–trifluoroethylene–chlorotrifluoroethylene) nanocomposites. Issue 4 (12th January 2018) - Han, Xianghui; Chen, Sheng; Lv, Xuguang; Luo, Hang; Zhang, Dou; Bowen, Chris R.
Abstract : A rigid liquid crystalline fluoride-polymer has been chosen to tailor the shell thickness of rGO to investigate the effect of interfacial thickness on the dielectric behavior of polymer conductive nanocomposites. Abstract : Polymer nanocomposites based on conductive fillers for high performance dielectrics have attracted increasing attention in recent years. However, a number of physical issues are unclear, such as the effect of interfacial thickness on the dielectric properties of the polymer nanocomposites, which limits the enhancement of permittivity. In this research, two core–shell structured reduced graphene oxide (rGO)@rigid-fluoro-polymer conducting fillers with different shell thicknesses are prepared using a surface-initiated reversible-addition–fragmentation chain transfer polymerization method, which are denoted as rGO@PTFMS-1 with a thin shell and rGO@PTFMS-2 with a thick shell. A rigid liquid crystalline fluoride-polymer poly{5-bis[(4-trifluoro-methoxyphenyl)oxycarbonyl]styrene} (PTFMS) is chosen for the first time to tailor the shell thicknesses of rGO via tailoring the degree of polymerization. The effect of interfacial thickness on the dielectric behavior of the P(VDF–TrFE–CTFE) nanocomposites with rGO and modified rGO is studied in detail. The results demonstrate that the percolation threshold of the nanocomposites increased from 0.68 vol% to 1.69 vol% with an increase in shell thickness. Compared to the rGO@PTFMS-1/P(VDF–TrFE–CTFE) composites, the rGO@PTFMS-2/P(VDF–TrFE–CTFE) composites exhibited a higher breakdown strength and a lower dielectric constant, which can be interpreted by interfacial polarization and the micro-capacitor model, resulting from the insulating nature of the rigid-polymer shell and the change of rGO's morphology. The findings provide an innovative approach to tailor dielectric composites, and promote a deeper understanding of the influence of interfacial region thickness on the dielectric performance.